CFD transient simulation of the cough clearance process using an Eulerian wall film model. Issue 2 (25th January 2017) - Paz, Concepción; Suárez, Eduardo; Vence, Jesús
Abstract: In this study, a cough cycle is reproduced using a computational methodology. The Eulerian wall film approach is proposed to simulate airway mucus flow during a cough. The reproduced airway domain is based on realistic geometry from the literature and captures the deformation of flexible tissue. To quantify the overall performance of this complex phenomenon, cough efficiency (CE) was calculated, which provided an easily reproducible measurement parameter for the cough clearance process. Moreover, the effect of mucus layer thickness was examined. The relationship between the CE and the mucus viscosity was quantified using reductions from 20 to 80%. Finally, predictions of CE values based on healthy person inputs were compared with values obtained from patients with different respiratory diseases, including chronic obstructive pulmonary disease (COPD) and respiratory muscle weakness (RMW). It was observed that CE was reduced by 50% in patients with COPD compared with that of a healthy person. On average, CE was reduced in patients with RMW to 10% of the average value of a healthy person.